1998
DOI: 10.1038/sj.sc.3100625
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic syringomyelia and post-traumatic spinal canal stenosis: A direct relationship: Review of 75 patients with a spinal cord injury

Abstract: This study aims to demonstrate predictive factors for post traumatic syringomyelia (PTS), and in particular to correlate the role of insu ciency of reduction of a spinal fracture with the occurrence of syringomyelia. One hundred and twenty-eight spinal cord injured patients (SCI) were studied during the years 1992 and 1993. Among them, 75 underwent a complete and reliable evaluation including: review of the initial vertebral lesion, and of the surgery report, and a radiological study of the lesion site with st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 21 publications
0
51
1
Order By: Relevance
“…However, other studies suggest that syringomyelia development may be associated with the injury site. Sgouros and Williams 17 found that 78% of syringomyelia patients had a thoracolumbar spinal injury, whereas El Masry et al 5 and PerrouinVerbe et al 9 concluded that cavities form more commonly in thoracic compared with cervical spinal cord injury patients. In contrast, Rossier et al, 14 Lyons et al, 18 and Vannemreddy et al 6 found that syringomyelia was more commonly associated with cervical spinal cord injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other studies suggest that syringomyelia development may be associated with the injury site. Sgouros and Williams 17 found that 78% of syringomyelia patients had a thoracolumbar spinal injury, whereas El Masry et al 5 and PerrouinVerbe et al 9 concluded that cavities form more commonly in thoracic compared with cervical spinal cord injury patients. In contrast, Rossier et al, 14 Lyons et al, 18 and Vannemreddy et al 6 found that syringomyelia was more commonly associated with cervical spinal cord injury.…”
Section: Discussionmentioning
confidence: 99%
“…Factors examined include: age at onset, gender, cause of injury, site of injury, severity of injury, type of vertebral fracture, treatment method and the degree of encroachment into the vertebral canal. 6,9 Complete spinal cord injury and arachnoiditis have been associated with an increased incidence of post-traumatic syringomyelia, and increasing age, damage at the cervical and thoracic levels, dislocated spinal fracture and the use of spinal instrumentation without decompression have all been identified as risk factors for the early development of posttraumatic syringomyelia. 6 To date, however, none of those factors have been established as being definitively causative.…”
Section: Introductionmentioning
confidence: 99%
“…At T 1 , spinal canal stenosis was measured using the method previously described by Perrouin-Verbe et al 2 The most recent MRI was examined to identify the post-traumatic spinal cord lesions using the criteria defined by Wang et al 8 At T 2 , the MRI that was performed because of the neurological worsening was assessed using the abovementioned criteria.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Cord tethering, defined as attachment of the spinal cord to the wall of the bony spinal canal, 8 is known to be a major factor in the occurrence of such a complication. [3][4][5]9,10 The long-term SCI patient follow-up highlights that PTM is a frequent complication among these patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation